Climate change and shifting distributions of medicinal and aromatic Lippia and Salimenaea species (Verbenaceae) in southern south America: a species distribution modelling approach - García, Santiago; Nores, María J.; De Diego, Fernando Carlos; Bach, Hernán Gerónimo; Peralta, Patricia Angelica; Robbiati, Federico O. (Meise Botanic Garden and the Royal Botanical Society of Belgium, 2025)
Background and aims – Climate change is driving biodiversity loss globally, including species with medicinal and aromatic properties. In this study, we assessed the potential distributions of three plants, Lippia alba, L. turbinata, and Salimenaea integrifolia, widely consumed in South America. In this study, we aimed i) to predict their current geographic distribution through SDM, ii) to estimate the importance of abiotic factors in their distribution, iii) to evaluate the potential change in future distribution under different scenarios of climate change. Material and methods – Using MaxEnt, we modelled the current and future potential distributions of these three species under three Representative Concentration Pathways (RCPs 2.6, 4.5, and 8.5) for the period 2070 (2061–2080). Key results – The distribution of L. alba is primarily influenced by precipitation seasonality and mean annual temperature, whereas L. turbinata and S. integrifolia are shaped by mean annual temperature and annual precipitation. The most favourable areas for L. alba are found in the Chacoan, Espinal, Pampean, Paranaense, Caatinga, Atlantic, and Amazonian biogeographic provinces (2,250,640 km2). Lippia turbinata thrives in the Chacoan, Espinal, Monte, Pampean, and Yungas provinces (671,851 km2), while S. integrifolia is best suited to the Monte, Chacoan, and Puna/Prepuna provinces (197,022 km2). Our results indicate heterogeneous responses to climate change in the future: L. turbinata and S. integrifolia may experience range expansion (15.12 to 19.86% and 1.48 to 3.46%, respectively), while L. alba is projected to face range contraction (-4.60 to -23.23%), particularly in the northern edge of its distribution. Conclusion – These findings emphasize the species-specific responses of medicinal and aromatic plants to climate change. Moreover, they highlight the need to develop tailored conservation strategies to safeguard vulnerable populations and preserve valuable medicinal resources.